2010
DOI: 10.1175/2009mwr3202.1
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Forcing Mechanisms of a Heavy Precipitation Event along the Alpine South Side Using Potential Vorticity Inversion

Abstract: Extreme precipitation events along the Alpine south side (AS) are often forced by upper-level positive potential vorticity (PV) anomalies over western Europe. These so-called PV streamers go along with a dynamical forcing for upward motion, a reduction of the static stability in the troposphere (hence facilitating convection), and are associated with low-level winds that transport moisture toward the Alps.A case of heavy precipitation is examined using the 40-yr ECMWF Re-Analysis data. Piecewise PV inversion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 51 publications
5
60
0
Order By: Relevance
“…By separating the large-scale flow into components associated with individual disturbances using techniques such as piecewise PV inversion [Schlemmer et al, 2010] or Helmholtz decomposition, one may further estimate precipitation due to individual systems.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…By separating the large-scale flow into components associated with individual disturbances using techniques such as piecewise PV inversion [Schlemmer et al, 2010] or Helmholtz decomposition, one may further estimate precipitation due to individual systems.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…For the calculation of CAPE, we rely on the operational post-processing routines for mixedlayer CAPE (layer depth 50 hPa) for the COSMO model (more information can be obtained from http://www.cosmo-model. org), which was adapted to the ECMWF setting by Schlemmer et al (2010). SRH is based upon the analysis of the tilting of horizontal vorticity into the vertical by Davies-Jones et al (1990).…”
Section: Ecmwf Analysis-synoptic Surrounding and Tornado Indicesmentioning
confidence: 99%
“…The examination of the PV structure is instructive in that anomalous, upper-level PV features can be associated with enhanced advection of low-level moisture, forced lifting and atmospheric destabilization (Funatsu and Waugh, 2008;Massacand et al, 1998;Hoinka and Davies, 2007;Schlemmer et al, 2010). With respect to jet stream/streak structure, it has been shown that the ageostrophic circulation associated with jet streaks can also result in forced lifting (Uccelini and Johnson, 1979;Rose et al 2004).…”
Section: Synoptic-scale Environment Of European Tornadoesmentioning
confidence: 99%
“…Massacand et al, 1998;Fehlmann and Quadri, 2000;Richard et al, 2003;Argence et al, 2008;Ducrocq et al, 2008;Nussier et al, 2008;Schlemmer et al, 2010) considered events in autumn or early winter, when the Mediterranean is still relatively warm. This can cause considerable evaporation of moisture, which may be transported towards the Alpine ridge due to the flow induced by an upper-level PV streamer and contribute to the occurrence of such heavy precipitation events.…”
Section: Introductionmentioning
confidence: 99%